Genetic Deletion of MT(1) Melatonin Receptors Alters Spontaneous Behavioral Rhythms in Male and Female C57BL/6 Mice - Adamah-Biassi, E.B. (Horm Behav, 2014)
Behaviors vary over the 24 hr. light/dark cycle and these temporal patterns reflect in part modulation by circadian neural circuits and hormones, such as melatonin. The goal of this study was to investigate if MT(1) melatonin receptors are involved in behavioral regulation by comparing male and female C57 wild type (WT) mice with C57 mice that had a genetic deletion of the MT(1) receptor (MT(1)KO). A comprehensive array of fifteen distinct spontaneous behaviors was recorded continuously in the homecage over multiple days using the HomeCageScan system. Behaviors assessed were activity-like (i.e. come down, hang, jump, walk), exploration-like (i.e. dig, groom, rear up, sniff, stretch), resting-like (i.e. awake, remain low, rest, twitch) and ingestion-like (i.e. drink, eat). Phenotypic array and temporal distribution analysis revealed distinct behavioral rhythms that differed between WT and MT(1)KO mice. The rhythms were consistent from day to day in males and varied with the estrous cycle in females. We also studied the role of MT(1) receptors on depressive and anxiety-like behaviors. Genetic deletion of MT(1) receptors increased immobility time in the forced swim test and decreased the number of marbles buried in the marble burying test in both male and female C57 mice. We conclude that MT(1) melatonin receptors are involved in neural pathways modulating diurnal rhythms of spontaneous behavior in the homecage as well as pathways regulating depressive and anxiolytic-like behaviors.